PERSEPSI SISWA TERHADAP PEMBINAAN KESISWAAN DI SEKOLAH MENENGAH ATAS (SMA) NEGERI KECAMAATAN GUNUNG TALANG - Dina Aldes Fatma (Jurnal Bahana Manajemen Pendidikan, 2015)
The purpose of this research is to know the information about the students perception about student development at senior high school Sub distric Gunung Talang. The population are 1279 students and the sample are 128 students those are taken random by using simple random sampling technique. The instrument of this research is quesioner with Likert scale models that have been tested. The data analyze through average score. The result of this research is perception of students above the student development at senior high school Sub district Gunung Talang is good category.Key word: Student development